Scooby-Doo! World of Mystery 52 Spain - Barcelona - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
Something big and fiery is scaring the workers away from Barcelona's famous church!The gang investigate...
Keywords: Juvenile literature-Fiction